Produkowanie estetyk, produkowanie podmiotu. Początki odwilży i wolność twórcza w sztukach wizualnych na przykładzie wystawy w Arsenale - Dąbrowski, Jakub (Artium Quaestiones, 2019)
In Polish art history, there are two approaches to the “Arsenał” exhibition of August 1955. One, rooted in the debates around it, presents the “Arsenał” as the beginning of a political “thaw” – an act of emancipation, a demonstration of young artists who rebelled against the socialist realism. The other approach to the show or, rather, to the “thaw” as a whole, rejects an interpretation of artistic processes and choices as autonomous activities. Instead, with reference to the theory of Michel Foucault, the “Arsenał” is considered as a result of a reconfiguration of scattered power relations, stimulated by the changing strategies of the institutional power system. The present paper follows the latter approach. Foucault claims that power relations are combined with three interconnected types of human relations: defining the hierarchy of tasks and division of labor, compelling obedience, and performing “communicative binding,” i.e. purposeful action that affects the actors’ knowledge of the world and of themselves. After 1954, power relations in Poland were strategically changing: the system of labor division and the distribution of art, including all the related benefits, was still centralized, but the ineffective administrative control relaxed, while the production of meaning changed as well – the communist party modified its rhetoric referring to art and the range of artistic choice grew together with the options of communication. Still, the liberalization of the system and abandoning the Moscow version of the socialist realism in cultural policy did not mean any real increase of the freedom of choice. Using state exhibition institutions and the press, which was the main channel of communication between the authorities and the masses, the communist regime continued to control the aesthetic consciousness of the artists. An analysis of both printed and visual messages found in the press of the period, specialist periodicals and daily newspapers alike, has revealed a surprising similarity of the official discourse and the aesthetic choices made by the participants of the “Arsenał” – in particular those choices which were later interpreted as attempts to reject the socialist realism and launch a new beginning. It seems that the young artists were “positively censored,” i.e. the regime succeeded in creating an aesthetic reality which they accepted. What is more, they considered it subversive as an emanation of liberty. The selection of the aesthetic modes favored by the authorities took place in an unconscious way already at the stage of creation, before particular works of art were accepted by the ”Arsenał” jury and before they were actually controlled by the institutions of censorship.